The alpha subunit of the human granulocyte-macrophage colony-stimulating factor receptor signals for glucose transport via a phosphorylation-independent pathway. - Ding, D X (1994)
The receptor for granulocyte-macrophage colony-stimulating factor (GM-CSF) is composed of an alpha and beta subunit, which together form the high-affinity receptor. The alpha subunit by itself binds ligand at low affinity, whereas the isolated beta subunit does not bind GM-CSF. It is generally believed that the high-affinity receptor is responsible for the multiple functions of GM-CSF and that the isolated alpha subunit (GMR alpha) does not transduce a signal. Xenopus laevis oocytes injected with RNA encoding human GMR alpha expressed up to 10(10) low-affinity sites for GM-CSF (Kd = 6 nM). GM-CSF binding to the alpha subunit expressed in Xenopus oocytes caused activation of 2-deoxyglucose transport through endogenous glucose transporters. 2-Deoxyglucose transport was stimulated by similar low concentrations of GM-CSF in HL-60 leukemia cells as well as normal human neutrophils and Xenopus oocytes expressing GMR alpha. Engagement of the isolated alpha subunit in oocytes did not lead to protein phosphorylation or tyrosine phosphorylation of mitogen-activated protein kinase (MAP kinase). Staurosporin and genistein inhibited GM-CSF-induced tyrosine phosphorylation of MAP kinase in human neutrophils and HL-60 cells without affecting GM-CSF-stimulated uptake of 2-deoxyglucose. These results provide direct evidence that the isolated alpha subunit signals for hexose transport and can do so without engagement of the kinase cascade. Our data also indicate that signaling for hexose uptake may occur in a phosphorylation-independent manner in cells expressing the high-affinity GM-CSF receptor.